Additional slipper lobsters of the subfamily Scyllarinae Latreille, 1825 (Crustacea, Achelata, Scyllaridae) from Taiwan - Yang, Chien-Hui; Lin, Chia-Wei; Chan, Tin-Yam (Zootaxa, 2014)
Five scyllarine lobsters are recorded from Taiwan for the first time. They are Bathyarctus rubens (Alcock & Anderson, 1894), Biarctus sordidus (Stimpson, 1860), Chelarctus aureus (Holthuis, 1963), Crenarctus bicuspidatus (De Man, 1905) and Petrarctus veliger Holthuis, 2002. The distributions of B. rubens, C. aureus and P. veliger are extended northwards to Taiwan. Distinguishing characters of these five species are illustrated and color photographs of all but B. sordidus are provided. Altogether, nine genera and 17 species of scyllarine lobsters are now known from Taiwan.